Integrating Resource-Based Theory and Contingency Theory for Enhancing Supply Chain Resilience in Malaysia: A Post-Pandemic Analysis - Narayanan, N. Sureshkumar PP; Ghapar, Farha; Chew, Li Lian; Kaliani Sundram, Veera Pandiyan; M.Naidu, Babudass; Daud, Azimah (Information Management and Business Review, 2024)
The COVID-19 pandemic has significantly disrupted global supply chains, exposed their vulnerabilities and underscored the urgent need for enhanced resilience. In Malaysia, the pandemic’s impact on supply chains has been profound, prompting a re-evaluation of existing strategies and frameworks. This study explores the integration of Resource-Based Theory (RBT) and Contingency Theory (CT) to enhance supply chain resilience in Malaysia. Through in-depth case studies and semi-structured interviews with senior managers and supply chain professionals, this research identifies key factors contributing to the successful implementation of an integrated resilience framework. The findings reveal that firms leveraging advanced technology, skilled workforce, and strategic partnerships can maintain operational efficiency and adaptability. Context-specific strategies such as diversifying suppliers, local sourcing, strategic stockpiling, and flexible logistics solutions are essential in responding to disruptions. Common challenges include high initial costs, coordination issues, regulatory hurdles, and cultural resistance to change. The integration of RBT and CT results in improved supply chain visibility, flexibility, robustness, and stakeholder collaboration. This study contributes to the academic discourse by offering practical insights for firms seeking to enhance supply chain resilience. It underscores the importance of combining internal strengths with adaptive strategies tailored to the external environment. The findings provide valuable guidance for both academia and industry in developing more robust and adaptive supply chain strategies in the post-pandemic landscape. Future research should explore the integration of RBT and CT across different contexts and industries and investigate the role of emerging technologies in enhancing supply chain resilience.